High‐Stretchability, Ultralow‐Hysteresis ConductingPolymer Hydrogel Strain Sensors for Soft Machines. Issue 32 (11th July 2022) - Shen, Zequn; Zhang, Zhilin; Zhang, Ningbin; Li, Jinhao; Zhou, Peiwei; Hu, Faqi; Rong, Yu; Lu, Baoyang; Gu, Guoying
Abstract: Highly stretchable strain sensors based on conducting polymer hydrogel are rapidly emerging as a promising candidate toward diverse wearable skins and sensing devices for soft machines. However, due to the intrinsic limitations of low stretchability and large hysteresis, existing strain sensors cannot fully exploit their potential when used in wearable or robotic systems. Here, a conducting polymer hydrogel strain sensor exhibiting both ultimate strain (300%) and negligible hysteresis (<1.5%) is presented. This is achieved through a unique microphase semiseparated network design by compositing poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) nanofibers with poly(vinyl alcohol) (PVA) and facile fabrication by combining 3D printing and successive freeze‐thawing. The overall superior performances of the strain sensor including stretchability, linearity, cyclic stability, and robustness against mechanical twisting and pressing are systematically characterized. The integration and application of such strain sensor with electronic skins are further demonstrated to measure various physiological signals, identify hand gestures, enable a soft gripper for objection recognition, and remote control of an industrial robot. This work may offer both promising conducting polymer hydrogels with enhanced sensing functionalities and technical platforms toward stretchable electronic skins and intelligent robotic systems. Abstract : A conducting‐polymer hydrogel strain sensor is proposed with both high stretchability (300% strain) and ultralow hysteresis (<1.5%). The hydrogel‐based sensor harnesses a unique microphase semiseparated network to achieve enhanced sensing properties. The fabricated sensor can be applied as electronic skins to monitor physiological signals, enable a soft gripper for object recognition and remote control of an industrial robot.